Generalized anxiety disorder in primary care: mental health services use and treatment adequacy. Issue 1 (December 2015) - Roberge, Pasquale; Normand-Lauzière, François; Raymond, Isabelle; Luc, Mireille; Tanguay-Bernard, Marie-Michèle; Duhoux, Arnaud; Bocti, Christian; Fournier, Louise
Abstract Purpose Generalized Anxiety Disorder (GAD) is a common mental disorder in the primary care setting, marked by persistent anxiety and worries. The aims of this study were to: 1) examine mental health services utilisation in a large sample of primary care patients; 2) explore detection of GAD and minimal standards for pharmacological and psychological treatment adequacy based on recommendation from clinical practice guidelines; 3) examine correlates of treatment adequacy, i.e. predisposing, enabling and needs factors according to the Behavioural Model of Health Care Use. Methods A sample of 373 adults meeting DSM-IV criteria for Generalized Anxiety Disorder in the past 12 months took part in this study. Data were drawn from the "Dialogue" project, a large primary care study conducted in 67 primary care clinics in Quebec, Canada. Following a mental health screening in medical clinics (n = 14833), patients at risk of anxiety or depression completed the Composite International Diagnostic Interview-Simplified (CIDIS). Multilevel logistic regression models were developed to examine correlates of treatment adequacy for pharmacological and psychological treatments. Results Results indicate that 52.5 % of participants were recognized as having GAD by a healthcare professional in the past 12 months, and 36.2 % of the sample received a pharmacological (24.4 %) and/or psychological treatment (19.2 %) meeting indicators based on clinical practice guidelines recommendations. The detection of GAD by a health professional and the presence of comorbid depression were associated with overall treatment adequacy. Conclusions This study suggests that further efforts towards GAD detection could lead to an increase in the delivery of evidence-based treatments. Key targets for improvement in treatment adequacy include regular follow up of patients with a GAD medication and access to psychotherapy from the primary care setting.